2015
DOI: 10.1590/0100-67622015000200014
|View full text |Cite
|
Sign up to set email alerts
|

Establishment Techniques for Tropical Legumes in the Understory of a Eucalyptus Plantation

Abstract: -This study evaluated establishment methods for a mixture of herbaceous forage legumes [Centrosema acutifolium, Clitoria ternatea, Pueraria phaseoloides, Stylosanthes Campo Grande (Stylosanthes capitata + S. macrocephala), Calopogonium mucunoides, Lablab purpureus, Arachis pintoi, and Aeschynomene villosa] under the shade of an Eucalyptus grandis plantation submitted to thinning (40%) 8 years after planting in Anhembi, São Paulo (22°40'S, 48°10'W, altitude of 455 m). The experiment started in December 2008 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…This findings were similar to those obtained in Nagekeo experiment, where the highest plant population was achieved in the dibbling technique treatment (42 plants/m²), followed by furrowed and unharrowed technique (34 plants/m²), then furrowed and harrowed (27 plants/m²), and the lowest was observed in the broadcast and harrowed (20 plants/m²). Nicodemo et al (2015) obtained that highest plant population was encountered in the broadcast on land treated with harrow before and after seeds were sown (28.5 plants/m²) while the lowest plant number (9.4 plants/m²) was obtained in the broadcast only technique without harrowing the land. At this we observed that the harrowed land provides good seed contact with the soil, and thus better seedling emergences.…”
Section: Plant Populationmentioning
confidence: 88%
“…This findings were similar to those obtained in Nagekeo experiment, where the highest plant population was achieved in the dibbling technique treatment (42 plants/m²), followed by furrowed and unharrowed technique (34 plants/m²), then furrowed and harrowed (27 plants/m²), and the lowest was observed in the broadcast and harrowed (20 plants/m²). Nicodemo et al (2015) obtained that highest plant population was encountered in the broadcast on land treated with harrow before and after seeds were sown (28.5 plants/m²) while the lowest plant number (9.4 plants/m²) was obtained in the broadcast only technique without harrowing the land. At this we observed that the harrowed land provides good seed contact with the soil, and thus better seedling emergences.…”
Section: Plant Populationmentioning
confidence: 88%